ANALISIS KUALITAS LABA PADA PERUSAHAAN KONTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Rokan, Mustafa Kamal; Nurwani, Nurwani; Gunawan, Asrul (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2025)
This study aims to determine the effect of profitability, leverage, and liquidity on earnings quality in construction companies and buildings listed on the Indonesia Stock Exchange (IDX). In this research using quantitative methods with an associative approach. Population that used is the company's annual financial statements buildings and buildings listed on the Indonesia Stock Exchange (IDX) period 2016-2020 as many as 18 companies. Sampling technique using purposive sampling technique based on certain criteria. Results research shows that profitability significant effect on earnings quality. Leverage has no significant effect on earnings quality. Liquidity no significant effect on earnings quality. Simultaneously, all the independent variables are profitability, leverage, and liquidity simultaneously significantly influence earnings qualityKeyword: Profitability, leverage, Liquidity on earnings quality